an Analysis and Recommendations for the Development of Micro, Small and Medium Enterprises (MSMEs) Warung Pesantren : Evaluation of Financial Performance, Marketing Strategies, and Identification of Opportunities and Challenges - Aziz, Fachmi Nur (Universitas Nusa Putra, 2025)
This journal analyzes and provides recommendations for the development of Micro, Small, and Medium Enterprises (MSMEs) in the context of boarding school stalls (Warung Pesantren). The study evaluates financial performance through key profitability metrics, revealing a gross profit margin of 0.80%, an operating profit margin of 0.28%, and a net profit margin of 0.80%, indicating tight profit conditions and limited operational efficiency. Despite these constraints, the marketing strategy employed is found to be highly relevant and feasible for implementation. The strategic approach focuses on strengthening market reach, improving customer engagement, and leveraging local community networks, all of which are practical for enhancing MSME performance. This research also identifies several opportunities and challenges faced by Warung Pesantren, offering tailored solutions to optimize their business growth. The findings provide valuable insights for stakeholders to enhance competitiveness and sustainability in similar MSME environments.